Exploring The Philosophy of Salam, Murabahah, and Istishna Agreements in Sharia Economic Law: Producer Protection and Economic Growth - Asmawi, Zaimmudin (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2023)
This research investigates the basic ideas behind Salam, Murabahah, and Istishna contracts in Islamic economic law, as well as how they can be used to protect producers and promote economic expansion. The research reveals that Salam, Murabahah, and Istishna contracts can protect producers through prepayment mechanisms, transparency of costs and profits, and flexibility in fulfilling customer wishes. This research was conducted through an analysis of existing literature. This protection can impact economic development by assisting producers in increasing their output, encouraging innovation, and improving overall efficiency. The findings of this study significantly affect the application of Islamic economic theory and public policy, and they call for further investigation into how Salam, Murabahah, and Istishna contracts can be utilized in real-world situations.